Board governance quality and risk disclosure compliance among financial institutions in Uganda. Issue 1 (16th October 2020) - Nkuutu, Geofrey; Ntayi, Joseph Mpeera; Nkote, Isaac Nabeeta; Munene, John; Kaberuka, Will
Abstract : Purpose: This paper aims to examine the impact of board governance quality (BGQ) and its mechanisms, namely board activity, board independence, board communication and board expertise, on the level of risk disclosure compliance (RDC) among financial institutions (FIs) in Uganda. Design/methodology/approach: The study adopts a cross-sectional design where data are collected through a questionnaire survey and audited financial statements of 83 FIs. The authors employ partial least square structural equation modeling (SmartPLS32.7) to test hypotheses. Findings: The authors find that the level of RDC in Ugandan FIs is low. Further, the study finds the positive relation between BGQ and RDC. Moreover, the authors find that RDC is positively and significantly related with board activity, board independence, board communication and board expertise. Furthermore, the authors find that the level of RDC is positively and significantly related to ownership type, firm size and board size, respectively. Nevertheless, industry type, number of branches and firm age are insignificantly related to RDC. Practical implications: The study provides relevant insights into regulators and policy makers with early symptoms of potential problems regarding weak board governance in FIs. Policy makers may also use these findings as a guideline tool for improving existing board governance frameworks in place and development of new disclosure policies. In addition, the study provides an input into the review and amendments of existing corporate governance codes for the regulators. Originality/value: This study offers the empirical evidence on the nexus between BGQ and RDC of FIs in Uganda. Moreover, the study also offers evidence on how BGQ mechanisms impact RDC. The study also further adds theoretical foundations to the RDC literature.